Food, Culture and Tourism: A Gastronomy Trilogy Enhancing Destination Marketing, case study of Odisha, India - Mohanty, P.P.; Rout, Himanshu Bhusan; Sadual, Sapan Kumar (AIBPM Publisher, 2020)
In the modern era, food mingled with culture and cultural subsets are one of the major tools for tourism destination marketing. Food, culture and tourism have the similar attributes that has formed a gastronomical trilogy differentiating traditional destination marketing from the modern day’s destination marketing. The gastronomical trilogy can be defined as a group of similar attributes forming a triangle where each one of them are dependent with each other and the role played by each one is influenced by the other. Hence in this paper, a strong relationship and dependency has been derived among food, culture and tourism for enhancement of destination development and marketing.